Optimization of Wet or Dry Micro-blasting on PVD Films by Various Al2O3 Grain Sizes for Improving the Coated Tools' Cutting Performance - K. -D. Bouzakis; A. Tsouknidas; G. Skordaris; E. Bouzakis; S. Makrimallakis; S. Gerardis; G. Katirtzoglou (Tribology in Industry, 2011)
Micro-blasting on PVD coated tools is an effective technology for improving their cutting performance. Through micro-blasting, compressive stresses are induced into the film, thus increasing the coating hardness, but its brittleness too. Simultaneously, abrasion phenomena are activated, which may lead to roughness augmentation, film thickness decrease and substrate revelation. In this way, for a successful process conduct, it is pivotal to adapt, among others, the applied micro-blasting pressure to the employed medium, air or water. The paper deals with the optimization of wet or dry micro-blasting pressure by various Al2O3 grain sizes for improving the coated tool’s wear resistance. The wear behaviour of coated and variously dry or wet micro-blasted tools was investigated in milling. Considering the grains’ penetration kinematics into the coated tool surface and the film deformation mechanisms during dry or wet microblasting by fine or coarse sharp–edged Al2O3 grains, optimum process pressures can be determined.